Re-Imagining Economic Sociology - Aspers, Patrik; Dodd, Nigel (Oxford University Press, 2015)
The purpose of this book is to explore new developments in the field of economic sociology. It contains cutting-edge theoretical discussions by some of the world's leading economic sociologists, with chapters on topics such as the economic convention, relational sociology, economic identity, economy and law, economic networks and institutions. The book is distinctive in a number of ways. First, it focuses on theoretical contributions, by pulling together and extending what the contributors believe to be the most important theoretical innovations within their own particular areas of the field. Second, there are contributions by leading economic sociologists from both the US and Europe, which gives the book both wider scope and appeal, while also creating the opportunity for some interesting dialogue between distinct theoretical traditions. The book will be of interest to researchers, Ph.D. students, and advanced students on both side of the Atlantic, and indispensible in advanced economic sociology courses.
Keywords: business & economics; economic sociology; economic theory; social science / sociology / general

Regulatory Transformations: Rethinking Economy-Society Interactions - Lange, Bettina; Haines, Fiona; Thomas, Dania (Bloomsbury Publishing, 2015)
The issue of whether transnational risk can be regulated through a social sphere goes to the heart of what John Ruggie has described as 'embedded liberalism': how capitalist countries have reconciled markets with the social community that markets require to survive and thrive. This collection, located in the wider debates about global capitalism and its regulation, tackles the challenge of finding a way forward for regulation. It rejects the old divisions of state and market, citizens and consumers, social movements and transnational corporations, as well as 'economic' and 'social' regulation. Instead this rich, multidisciplinary collection engages with a critical theme-the idea of harnessing the regulatory capacity of a social sphere by recognising the embeddedness of economic transactions within a social and political landscape. This collection therefore explores how social norms, practices, actors and institutions frame economic transactions, and thereby regulate risks generated by and for business, state and citizens.A key strength of this book is its integration of three distinct areas of scholarship: Karl Polanyi's economic sociology, regulation studies and socio-legal studies of transnational hazards. The collection is distinct in that it links the study of specific transnational risk regulatory regimes back to a social–theoretical discussion about economy–society interactions, informed by Polanyi's work. Each of the chapters addresses the way in which economics, as well as economic and social regulation, can never be understood separately from the social, particularly in the transnational context.Endorsement'This thought-provoking collection asks the most critical question of our time – how to civilise markets through social accountability and political action. The climate and financial crises we face show how crucial this challenge is. Lange, Haines and Thomas have put together a series of fruitful case studies of the possibilities for embedding economic relationships in social relationships by a series of top-class researchers within their own illuminating and sensitive framing of the issue'.Professor Christine Parker, Professor of Regulatory Studies at Monash University.
Keywords: administrative law & regulatory practice; economic regulation; economic sociology; embedded liberalism; social regulation; socio-legal studies

Corporate Power and Responsible Capitalism?: Towards Social Accountability - Jones, Bryn (Edward Elgar Publishing, 2015)
In this important book, Bryn Jones uses insights from political economy, historical analysis and sociological concepts of the corporation, as a socially disembedded but political actor, to address concerns over the over-reach of Anglo-Saxon corporation KM -- on page 6: "Following Karl Polanyi, I argue that ST/EM firms have outgrown and threaten to dominate, envelop and even undermine, some of the social and political institutions on which a sustainable market economy depends. Any rebalancing of the relationship between corporations and the rest of society must therefore interrogate the nature of the relationship between market organisations, such as firms, and the social institutions to which they are linked.
Keywords: ST/EM corporations; business & economics; business ethics; business systems; corporate governance; disembedding; executive managed corporations; industrial management; management; management science; organizational behavior; share-traded corporations; social embedding

The Great Mindshift: Linking Forerunners of a New Sustainability Paradigm - Gopel, Maja (Brookings Inst Press, 2015)
Making sustainability a policy goal is one of the greatest challenges of the 21st century. Calls for a paradigm shift are becoming increasingly frequent and urgent. In fact, change toward a sustainable form of society seems to be more within reach than ever before. The mindset of people has changed in the course of economic and environmental crises. This publication presents the current scientific and practical approaches that shape and empower the process of change toward true sustainability. It also raises the question as to the new possibilities that may arise from linking these approaches.
Keywords: environmental policy; environmental science; global warming & climate change; public policy; science

The Evolution of the Property Relation: Understanding Paradigms, Debates, and Prospects - Davis, Anne E. (Springer, 2015)
Evolution of the Property Relation defines an approach to economics which is centered around the concept of property and explores the historical evolution of the relationship of the individual, private property, and the state, and the distinctive changes wrought by the emergence of the market.
Keywords: business & economics; economic development; economic history; economic theory; labor; labour; management; organizational behavior; social science; sociology; strategic planning